Hydrolytic cleavage of glycosidic bonds for cellulose nanoparticles (CNPs) production by BmimHSO4 ionic liquid catalyst - Low F.W.; Samsudin N.A.; Yusoff Y.; Tan X.Y.; Lai C.W.; Amin N.; Tiong S.K. (Elsevier B.V., 2023)
Cotton; Crystallinity; Crystallite size; High resolution transmission electron microscopy; Hydrolysis; Ionic liquids; Nanoparticles; Natural fibers; Sulfur compounds; Sustainable development; Synthesis (chemical); Textile fibers; Thermodynamic stability; Cellulose nanoparticles; Crystalline cellulose; Hazardous wastes; Hydrolysis methods; Hydrolysis process; Hydrolytic cleavage; Microcrystalline cellulose; Regenerate; Cellulose; Cotton; Crystallinity; Hydrolysis; Natural Fibers; Sulfur Compounds; Textile Fibers